2009
DOI: 10.1080/02646830802350831
|View full text |Cite
|
Sign up to set email alerts
|

The effect of post‐natal symptoms of post‐traumatic stress and depression on the couple's relationship and parent–baby bond

Abstract: Objectives:Research has shown that between 1 and 3% of women may suffer from post-traumatic stress disorder (PTSD) following childbirth. However, the potential effect of childbirth on fathers, and the implications of postnatal symptoms of PTSD for family relationships have received little attention. The current study therefore examined the potential effects of PTSD symptoms on the couple's relationship and parent-baby bond. Design: Internet based questionnaire study. Methods: One hundred and fifty two parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
130
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 48 publications
10
130
1
2
Order By: Relevance
“…There is also evidence of negative effects of anxiety on the parent-baby relationship and child outcomes (Feldman et al, 2009;Glasheen, Richardson & Fabio, 2010, for a review). Finally, studies also suggest that PTSD following childbirth may be linked to problems in the parent-baby relationship (Ballard, Stanley & Brockington, 1995;Nicholls & Ayers, 2007;Parfitt & Ayers, 2009). …”
Section: Parental Mental Health and Parent-infant Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence of negative effects of anxiety on the parent-baby relationship and child outcomes (Feldman et al, 2009;Glasheen, Richardson & Fabio, 2010, for a review). Finally, studies also suggest that PTSD following childbirth may be linked to problems in the parent-baby relationship (Ballard, Stanley & Brockington, 1995;Nicholls & Ayers, 2007;Parfitt & Ayers, 2009). …”
Section: Parental Mental Health and Parent-infant Interactionsmentioning
confidence: 99%
“…It consists of 17 items (5 intrusion, 7 avoidance and 5 arousal items) and has previously been used in relation to childbirth (e.g., Parfitt & Ayers, 2009;Sawyer & Ayers, 2009). Items are scored on a continuous 4-point scale with a total range of 0 -51, with higher scores indicating a greater symptom severity.…”
Section: Mental Healthmentioning
confidence: 99%
“…9 A negative birth experience can also lead to symptoms of post-traumatic stress disorder (PTSD). 14 Involving fathers in childbirth may result in a range of positive effects, such as being able to better manage their overwhelming feelings of helplessness or experiencing the first contact with their child more positively. 9 Besides fathers, mother and child benefit as well when the father is part of the childbearing process.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence from quantitative studies is mixed and available studies have been based on small or self-selected samples. For example, an online survey of 152 parents (126 women and 26 men) found that symptoms of PTSD and depression were associated with a poorer parent-baby bond (Parfitt and Ayers, 2009). However, another study of 64 couples recruited from birth registers at a UK hospital found no association between PTSD symptoms and the mother-baby bond, although there were small correlations between PTSD symptoms and an unfavorable father-baby bond (Ayers et al, 2007).…”
Section: Introductionmentioning
confidence: 99%